Parametric Modelling Techniques for Rhine Castle Models in Blender - Etienne Sommer; Mathieu Koehl; Pierre Grussenmeyer (Heritage)
Recent advances in 3D modelling have greatly improved the digital reconstruction of historic buildings. Traditional 3D modelling methods, while accurate, are very time-consuming and require a detailed focus on complex architectural features. The use of Building Information Modelling (BIM) technology, adapted to historic buildings as Historic Building Information Modelling (HBIM), has made the modelling process easier. However, HBIM still struggles with a lack of detailed object libraries that truly represent the diverse architectural heritage, due to the unique designs of these ancient structures. This article presents a new method using Blender software, focusing on Geometry Nodes and modifier tools for parametric modelling. This method aims to efficiently reconstruct the Rhine region’s castles, which are part of Europe’s most heavily fortified areas with a history that goes back to the <semantics>XIth</semantics> century. Many of these castles, over 500 years old, are now ruins. Our method allows for quick changes and detailed customization to meet the specific needs of archaeologists and heritage researchers. Developed as part of the Châteaux Rhénans-Burgen am Oberrhein project, funded by the European Interreg VI programme, this approach focuses on digitizing and promoting the Rhine castles’ heritage. The project aims to fill some gaps in parametric modelling by providing a flexible and dynamic toolset for heritage conservation.